ظاهرة التنمر لدى الأطفال - الدوسري، ريم (حليمة عبدالرمي, 2023)
تتصف ظاهرة التنمر بأنها من أخطر الظاهر انتشارا خصوصا مع انتشار وسائل التواصل الاجتماعي والألعاب الإلكترونية، وما يميزها أنها تتكرر يوميا حتى تترسخ في الذهن. بمعنى أنها قد تحدث أكثر من مرة، إذ يفترش المتنمر أنه الأقوى دائما فيلجأ إلى العنف والإيذاء من أجل التسلط على الآخرين والتحكم بهم طول الوقت بل وإذلالهم. التنمر من السلوكيات التي تنتشر بشكل كبير بين الأطفال والتي للأسف تحمل آثاراً سلبية عميقة على نفسية الطفل ومستقبله. The phenomenon of bullying is characterized as one of the most dangerous and widespread phenomena, especially with the spread of social media and electronic games, and what distinguishes it is that it is repeated daily until it becomes ingrained in the mind. This means that it may happen more than once, as the bully assumes that he is always the strongest, so he resorts to violence and abuse in order to dominate others. Controlling them all the time and even humiliating them. Bullying is one of the behaviors that is widely spread among children and unfortunately has profound negative effects on the child’s psychology and future.
Keywords: ظاهرة التنمر -- الألعاب الإلكترونية -- التنمر الإلكتروني -- الاضطرابات الشخصية -- رياض الأطفال